A coordenação pedagógica e o processo de inclusão do aluno com necessidade educacionais especiais:Um estudo de caso - Lira, Eleide Gomes Teixeira Torres (2012)
The school inclusion presents a number of challenges that has been mobilizing initiatives and studies about its effectiveness. If on one hand in such studies and initiatives it becomes important to emphasize on the role and training of teachers, on the other, there is few studies about the role (and performance) of the pedagogical coordination in face of this process. In this sense, this research focuses on the role of educational coordination in face of the school inclusion of students with Special Educational Needs (SEN) and it undertakes the following study s questions: has the action by the coordinator contributed to the process of including students with Special Educational Needs? How is it presented in the process of inclusion of students with SEN in regular education? And it aims to: investigate the role of the pedagogical coordinator in the process of inclusion of students with Special Educational Needs of Primary Education at regular schools; and to analyze the limits and possibilities of the coordinator actions in the process of inclusion of students with SEN. For the effectiveness of the research, a state school of Elementary School located at the city of Natal/RN was taken as an empiric field. It was selected as research subjects 4 coordinators, 2 teachers of the Multifunctional Resources Room and 2 teachers of 6th to 9th grades. The methodological approach that was used in this research is consistent with the qualitative approach, and it is configured as a case study, as it is understood that this type of research responds to the objective of the study, assuming the observation of everyday school life, the educational document analysis and interviews with the subjects as procedures and tools to build data. The construction and analysis of the data were followed by a dialogue with the literature dedicated to coordinating education and school enrollment. Considering the responsibilities of the contemporary pedagogical coordination due to the challenges and possibilities of schooling for all students, specially regarding to what is referred as collaborative work and ongoing training of teachers, this study points out to the lack of an articulated action related to the school inclusion process, considering the monitoring of the teaching activity and its dialogue with the Multifunctional Resources Room. Moreover, the emphasis on meeting the daily school routines and the compliance with bureaucratic procedures, put it into second, restructuring of the Political-Pedagogical and the possibility of mobilization of school around the problematization and systematization of an inclusive school project. The effectiveness of school s inclusion, therefore, implies the scaling of the functions of the pedagogical coordination, as well as the reorganization of the school it self, to ensure the mediation of collaborative actions, contemplating the teachers continuing education, having as a landmark difficulties, problems and experiences constructed in the school context